Three Sets of Characteristics of Chinese Anti-pandemic Literature: Realism Versus Postmodernism; Instrumentality Versus Artistry; and Nationalism Versus Liberalism - Bo, Yang; Kohler, Kyle; Rungruang, Apichai; Yanhong, Mu; Netthanyakonwong, Amornrat; Kittijarukhajorn, Sirirat (วารสารศิลปศาสตร์ มหาวิทยาลัยธรรมศาสตร์, 2024)
Through analyzing and studying a large number of Chinese anti-pandemic literary works, this paper finds that Chinese anti-pandemic literature exhibits three sets of distinctly opposing characteristics in terms of its creation method, literary value, and ideology. In terms of creative methods, official publications are mostly realist works, embodying realistic depictions of life, profound analyses of human nature, and reflections of social problems. On the other hand, Internet works have postmodernist features such as fragmentation and popularization. In terms of literary value, anti-pandemic literature demonstrates a powerful instrumentality, soothing people’s spirits through the power of literature, conveying to readers the knowledge and experience of fighting pandemics, and promoting the spirit of human solidarity, but it has artistic inadequacies such as the modulation and snackification of literary creation, and the roughness of language. In terms of ideology, anti-pandemic literature calls on people to pay attention to the rights of vulnerable groups in society, reflect on the government’s actions during the pandemic, and explore the relationship between people and the government. But more than that, it reflects the rivalry between China and the United States in terms of ideology and anti-pandemic narrative. The struggle between nationalism and liberalism is at its core. Overall, the emergence of Chinese anti-pandemic literature not only fills the gap in pandemic-related literature but also provides people with a perspective to see the deeper reality behind the pandemic through the manifestation of creation method, literary value, and ideology.